Berbagai Pencitraan Radiografik Sendi Temporo Mandibula - Menik Priaminiarti; Achmad Alhamid; Hanna Bachtiar Iskandar (Faculty of Dentistry, Universitas Indonesia, 2015)
Since temporomandibular joint (TMJ) is located close to the basis cranii, radiograpchic interpretation is difficult due to overlapping with bone structures of the skull adjacent to this area. Temporomandibular disorderes need accurate diagnosis. In accordance with advances in science and technology, radiographic investigation of TMJ has developed recently, either modified conventional techniques or the modern diagnostic ones. Transcranial lateral oblique projection is one of the conventional radiographic projections that usually used. In this projection, one could see the radiographic appearance of eminentia articulare, glenoid fossa, and head of the condyle antero-posteriorly. An appropriate radiographic examination technique chosen, could give more valuable diagnostic information needed.